2013
DOI: 10.1200/jco.2013.31.4_suppl.69
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy analyses of a randomized phase III clinical trial of combined therapy with CPT-11/CDDP versus CPT-11 alone in patients with advanced or recurrent gastric cancer refractory to prior S-1 chemotherapy.

Abstract: 69 Background: There has been no established regimen as the second-line treatment for advanced gastric cancer (AGC), though CPT-11 showed survival benefit over BSC. Combination of CPT-11 with CDDP is one of the promising regimens as the second-line chemotherapy after S-1 mono-therapy. Methods: This is a prospective, multicenter randomized phase III study comparing CPT-11+CDDP (Arm A) vs. CPT-11 alone (Arm B) in patients with advanced or recurrent gastric cancer resistant to S-1 mono-therapy or prior adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Notably, the proportion of patients receiving third-line therapy was the same (75%) in both groups. The results of another randomized trial (ECRIN) have been reported in the abstract form [18], in which irinotecan plus cisplatin (n=84) was compared with irinotecan alone (n=84) in patients refractory to an S-1 containing regimen. WJOG 4007 [19] is a RCT comparing weekly paclitaxel (n=108) with biweekly irinotecan (n=111) in GC patients refractory to fluoropyrimidines plus cisplatin.…”
Section: Seeking the Best Regimen Of Second-line Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the proportion of patients receiving third-line therapy was the same (75%) in both groups. The results of another randomized trial (ECRIN) have been reported in the abstract form [18], in which irinotecan plus cisplatin (n=84) was compared with irinotecan alone (n=84) in patients refractory to an S-1 containing regimen. WJOG 4007 [19] is a RCT comparing weekly paclitaxel (n=108) with biweekly irinotecan (n=111) in GC patients refractory to fluoropyrimidines plus cisplatin.…”
Section: Seeking the Best Regimen Of Second-line Therapymentioning
confidence: 99%
“…The agents investigated by these trials include chemotherapeutic drugs [17][18][19][20], a molecular targeting agent [21], and their combinations [22][23][24][25][26].…”
Section: Seeking the Best Regimen Of Second-line Therapymentioning
confidence: 99%